Protótipo para consulta paramétrica aos índices urbanísticos com suporte nas tecnologias BIM e GIS: o caso da cidade de João Pessoa - Farias Júnior, Antonio Gonçalves de (2019)
The choice of land for the development of an architectural project located in an urban space may require consulting a set of different laws to understand which aspects described in these documents will interfere with the project. Because they are essentially legislative texts, their contents are accessed individually in manual consultations. However, although there are already municipalities that make some databases available digitally, there is no integration between them allowing an optimization of your query. Studies that focus efforts on the creation of systems with automatic checks in search of a reduction of the time of these tasks and consistency in the results have been expanded. Thus, Building Informatio Modeling (BIM) technology emerges as a configurable system capable of storing a building information data structure, and Geographic Information System (GIS) technology for cartographic map database support. Delimited the object of study to the process of consultation of the urbanistic indexes of the Urbanism Code of the city of João Pessoa, this research proposes the development of a prototype of a system capable of generating automatic queries from the land location in GIS / Web environment. and calculation of constructive potential estimation in BIM environment, from the planimetric topography of convex polygonal terrain. The methodology had as data collection a documentary analysis to the urbanism code to describe its current consultation process, followed by systematic observations to propose a parametric model, and the application of a questionnaire for its validation with the participation of architecture students enrolled in project disciplines. The results showed differences between GIS and BIM technologies regarding the query time optimization capacity using the prototype and consistency in the delivery of results. Despite the limitations found in their implementation, the technologies pointed out several potentialities regarding the support tools in the design decision making from the visualization and understanding of the constructive constraints in their proposed digital environments.